2018
DOI: 10.3390/ma11071128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Synthetic Nano-CaO-Al2O3-SiO2-H2O Gel on the Early-Stage Shrinkage Performance of Alkali-Activated Slag Mortars

Abstract: The relatively high shrinkage of the alkali-activated slag (AAS) has restricted its application as a widely-used building material. This research attempts to study the effect of a hydrothermally synthesized C-A-S-H gel, which has a similar composition to that of the main AAS product, on the shrinkage performance of the AAS. The C-A-S-H nano-particles were mixed into AAS mortars in a proportion ranging from 1 wt % to 5 wt % using two different methods, and the drying and autogenous shrinkage ratio of modified A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Low crystallinity K-A-S-H gels and zeolite crystalline powders were synthesized and the differences and similarities of their (micro) structures were analyzed. Our previous studies [3,7] have demonstrated the synthetic C-A-S-H gel can be regarded as a chemical intensification of the hardening effect in alkali-activated binders, which also refine the pore structures of the alkali-activated binders and provide a novel approach of alkali-activated binders shrinkage reduction at an early stage. Meanwhile, these gels and the hydration products of alkali-activated materials have similar composition and morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low crystallinity K-A-S-H gels and zeolite crystalline powders were synthesized and the differences and similarities of their (micro) structures were analyzed. Our previous studies [3,7] have demonstrated the synthetic C-A-S-H gel can be regarded as a chemical intensification of the hardening effect in alkali-activated binders, which also refine the pore structures of the alkali-activated binders and provide a novel approach of alkali-activated binders shrinkage reduction at an early stage. Meanwhile, these gels and the hydration products of alkali-activated materials have similar composition and morphology.…”
Section: Discussionmentioning
confidence: 99%
“…The proportions of nano-SiO 2 , nano-Al 2 O 3 , KOH, and deionized water are shown in Table 1. Nanoscale K-A-S-H gel was synthesized according to our previous hydrothermal method [3,4]. The samples are named as follows: using K-A-S-H1.0 1 -1d-95 as an example, the K-A-S-H1.0 indicates a K 2 O/SiO 2 ratio in the K-A-S-H system of 1.0, the subscript indicates a SiO 2 /Al 2 O 3 ratio of 1, the 1d indicates a curing time of 1 day, and the 95 indicates that the material was cured at a temperature of 95 • C.…”
Section: Synthesis Of K-a-s-hmentioning
confidence: 99%
“…Various methods have been attempted to reduce the drying shrinkage of AAS. For example, the addition of fiber [60][61][62][63], pozzolanic material [57][58][59][60][61][62][63][64][65][66][67], an expansion agent [68][69][70], nano-materials [57,[71][72][73], a shrinkage-reducing agent (SRA) [32,34,[74][75][76][77], superabsorbent polymer [78,79], and methods for increasing the curing temperature [23,42,58,80,81] have been attempted. Previous studies on drying shrinkage reduction experiments and studies have shown a certain level of shrinkage reduction effect.…”
Section: Introductionmentioning
confidence: 99%